Head and neck burns are associated with long-term patient-reported dissatisfaction with appearance: A Burn Model System National Database study. Issue 2 (March 2019) - Sinha, I.; Nabi, M.; Simko, L.C.; Wolfe, A.W.; Wiechman, S.; Giatsidis, G.; Bharadia, D.; McMullen, K.; Gibran, N.S.; Kowalske, K.; Meyer, W.J.; Kazis, L.E.; et al.
Highlights: Adults with H&N burns demonstrated great dissatisfaction with their appearance and worse mental health outcomes than those with non-H&N burns. Adults with H&N burns had community integration, physical health, and satisfaction with life outcomes similar to those with non-H&N burns. Results suggest an opportunity for strategies and/or interventions to address satisfaction with appearance and mental health after H&N burn injury. Abstract: Introduction: Burns affecting the head and neck (H&N) can lead to significant changes in appearance. It is postulated that such injuries have a negative impact on patients' social functioning, quality of life, physical health, and satisfaction with appearance, but there has been little investigation of these effects using patient reported outcome measures. This study evaluates the effect of H&N burns on long-term patient reported outcomes compared to patients who sustained burns to other areas. Methods: Data from the National Institute on Disability, Independent Living, and Rehabilitation Research Burn Model System National Database collected between 1996 and 2015 were used to investigate differences in outcomes between those with and without H&N burns. Demographic and clinical characteristics for adult burn survivors with and without H&N burns were compared. The following patient-reported outcome measures, collected at 6, 12, and 24 months after injury, were examined: satisfaction with life (SWL), community integration questionnaire (CIQ), satisfaction with appearance (SWAP), short form-12 physical component score (SF-12 PCS), and short form-12 mental component score (SF-12 MCS). Mixed regression model analyses were used to examine the associations between H&N burns and each outcome measure, controlling for medical and demographic characteristics. Results: A total of 697 adults (373 with H&N burns; 324 without H&N burns) were included in the analyses. Over 75% of H&N injuries resulted from a fire/flame burn and those with H&N burns had significantly larger burn size (p < 0.001). In the mixed model regression analyses, SWAP and SF-12 MCS were significantly worse for adults with H&N burns compared to those with non-H&N burns (p < 0.01). There were no significant differences between SWL, CIQ, and SF-12 PCS. Conclusions: Survivors with H&N burns demonstrated community integration, physical health, and satisfaction with life outcomes similar to those of survivors with non-H&N burns. Scores in these domains improved over time. However, survivors with H&N burns demonstrated worse satisfaction with their appearance. These results suggest that strategies to address satisfaction with appearance, such as reconstructive surgery, cognitive behavior therapy, and social skills training, are an area of need for survivors with H&N burns.